Long-Term Evolocumab in Patients With Established Atherosclerotic Cardiovascular Disease. Issue 15 (29th August 2022) - O'Donoghue, Michelle L.; Giugliano, Robert P.; Wiviott, Stephen D.; Atar, Dan; Keech, Anthony; Kuder, Julia F.; Im, KyungAh; Murphy, Sabina A.; Flores-Arredondo, Jose H.; López, J. Antonio G.; Elliott-Davey, Mary; Wang, Bei; et al.
Abstract : Background: In FOURIER (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk), the proprotein convertase subtilisin-kexin type 9 inhibitor evolocumab reduced low-density lipoprotein cholesterol (LDL-C) and risk of cardiovascular events and was safe and well tolerated over a median of 2.2 years of follow-up. However, large-scale, long-term data are lacking. Methods: The parent FOURIER trial randomized 27 564 patients with atherosclerotic cardiovascular disease and LDL-C ≥70 mg/dL on statin to evolocumab versus placebo. Patients completing FOURIER at participating sites were eligible to receive evolocumab in 2 open-label extension studies (FOURIER-OLE [FOURIER Open-Label Extension]) in the United States and Europe; primary analyses were pooled across studies. The primary end point was the incidence of adverse events. Lipid values and major adverse cardiovascular events were prospectively collected. Results: A total of 6635 patients were enrolled in FOURIER-OLE (3355 randomized to evolocumab and 3280 to placebo in the parent study). Median follow-up in FOURIER-OLE was 5.0 years; maximum exposure to evolocumab in parent plus FOURIER-OLE was 8.4 years. At 12 weeks in FOURIER-OLE, median LDL-C was 30 mg/dL, and 63.2% of patients achieved LDL-C <40 mg/dL on evolocumab. Incidences of serious adverse events, muscle-related events, new-onset diabetes, hemorrhagic stroke, and neurocognitive events with evolocumab long term did not exceed those for placebo-treated patients during the parent study and did not increase over time. During the FOURIER-OLE follow-up period, patients originally randomized in the parent trial to evolocumab versus placebo had a 15% lower risk of cardiovascular death, myocardial infarction, stroke, or hospitalization for unstable angina or coronary revascularization (hazard ratio, 0.85 [95% CI, 0.75–0.96]; P =0.008); a 20% lower risk of cardiovascular death, myocardial infarction, or stroke (hazard ratio, 0.80 [95% CI, 0.68–0.93]; P =0.003); and a 23% lower risk of cardiovascular death (hazard ratio, 0.77 [95% CI, 0.60–0.99]; P =0.04). Conclusions: Long-term LDL-C lowering with evolocumab was associated with persistently low rates of adverse events for >8 years that did not exceed those observed in the original placebo arm during the parent study and led to further reductions in cardiovascular events compared with delayed treatment initiation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifiers: NCT02867813 and NCT03080935.